Neither IL-17A mRNA Nor IL-17A Protein Are Detectable in Langerhans Cell Histiocytosis Lesions - Peters, Tricia L (Nature Publishing Group, 2011)
Langerhans cell histiocytosis (LCH) is a rare disease characterized by heterogeneous lesions including CD207(+)/CD1a(+) dendritic cells that can result in significant morbidity and mortality. The etiology of LCH remains speculative, and neoplastic and inflammatory origins have been debated for decades. A recent study identified abundant interleukin-17 (IL-17A) protein in dendritic cells in LCH lesions as well as in plasma from patients with active disease. Furthermore, it identified dendritic cells as a novel source of IL-17A expression. However, subsequent studies from our research group failed to identify any IL-17A gene expression from CD207(+) dendritic cells or CD3(+) T cells in LCH lesions. In this study, further investigation once again fails to identify any cells in LCH lesions with IL-17A gene expression. Furthermore, IL-17A antigen is undetectable in LCH lesion lysates with western blotting, immunoprecipitation, spectral analysis, and enzyme-linked immunosorbent assay (ELISA). Western blots, immunoprecipitation, and ELISA experiments also demonstrate that antibodies used in original studies that established the IL-17A hypothesis for pathogenesis of LCH recognize nonspecific proteins. We conclude that evidence for IL-17A as a significant factor in LCH remains inadequate and clinical trials targeting IL-17A remain unjustified.